METHODOLOGY OF TRAINING FUTURE SPEECH THERAPISTS TO DIAGNOSE VERBAL AND NONVERBAL COMMUNICATION SKILLS OF MENTALLY RETARDED PRIMARY GRADE STUDENTS - Sayfullayeva I. Q. (Modern American Journals, 2025)
This article describes a methodology for training future speech therapists to diagnose verbal and nonverbal communication skills in primary school students with mental retardation.
Keywords: Future speech therapist, independent learning, practical and lecture classes, pedagogical process, verbal and nonverbal communication.